Coexistence of plasmid-mediated quinolone resistance determinants and AmpC-Beta-Lactamases in Escherichia coli strains in Egypt - Abd El-Aziz, N K; Gharib, A A (Cellular and Molecular Biology, 2015)
Three kinds of plasmid-mediated quinolone resistance (PMQR) determinants (qnr genes, qepA and aac(6')-Ib-cr) have been discovered and shown to be widely distributed among clinical isolates. To characterize the prevalence of PMQR determinants among AmpC-producing E. coli strains in food-producing animals and animal by-products in Egypt, twenty-nine E. coli strains were tested for their susceptibilities to antimicrobials and screened for PMQR determinants and AmpC Beta lactamases using PCR and plasmid profiling. It was found that qnr genes being detected alone or in combination with qepA or aac(6')-Ib-cr genes in 11 (37.9%) strains comprising 9 for qnrA and only one for both qnrB and qnrS. Moreover, qepA and aac(6')-Ib-cr were detected in 41.38% and 3.45% of E. coli strains, respectively. The ampC Î²-lactamase genes were detected in 75.86 % of all strains and in 100% and 53.3% of the PMQR determinant-positive and negative strains, respectively. In several cases, plasmid profiling of E. coli strains exhibiting the coexistence of both PMQR determinants and ampC genes on a single plasmid as a first report in Egypt that may contribute to rapid spread and increase in bacterial resistance, which is important to public health concern.